Takaful, Zakat and Waqf Instruments in Ensuring Holistic Senior Citizens Program Development in Malaysia - Rusni Hassan; Adnan Yusoff; Asral Widad Ahmad Asnawi; Ieman Sofiyya Adnan (Journal of Islamic Finance, 2020)
Malaysia will face the phenomenon of aging nation in 2040. In 2020 alone, the elderly in Malaysia is expected to reach 3.21 million people. The current of modernization greatly changes the structure of the Malaysian family whereby children are not able to take care of their old parents due to high demand of work and life. The work culture in Malaysia demands that employees to put priority on works and thus less focus on their family and elderly parents. Not only that the work opportunities that are mainly based in the cities and central areas require the young to travel and migrate far from their parent’s residence, leaving the elderly parents unattended. This phenomenon requires urgent attention and consideration from the government and relevant bodies to plan for the future of the elderly Malaysian. This paper aims to first, appraise the role of Takaful, Waqf and Zakat in helping and supporting the elderly or senior citizens in Malaysia. Second is to propose Takaful, Waqf and Zakat as instruments to provide financial assistance and protection to the elderly community. Third is to propose how these three instruments can be integrated for the utmost protection of policy holders and their beneficiaries when they reach the golden age.